A Perspective on the Commercial Viability of Perovskite Solar Cells. Issue 11 (4th November 2021) - Ling, JinKiong; Kizhakkedath, Pradeep Kumar Koyadan; Watson, Trystan M.; Mora-Seró, Iván; Schmidt-Mende, Lukas; Brown, Thomas M.; Jose, Rajan
Abstract : Perovskite Solar Cells In article number 2100401, Iván Mora‐Seró, Rajan Jose, and co‐workers present a roadmap for the perovskite solar cells via a 5S (Stability, Safety, Scalability, Sustainability, and Storage) analysis. Application driven, instead of performance driven, developments are shown to favor their commercialization.